Zooming in on scientific practices and evidence-based explanations during teaching NOS: A study in pre-service teacher education program - Deniz Saribas; Gaye Defne Ceyha; Doug Lombardi (Elementary Education Online, 2023)
Investigating pre-service science teachers’ tendency for emphasizing nature of science in their lesson plans is crucial. Students should construct scientific explanations based on data-based evidence gathered from the activities they actively engage in a discourse environment. Focusing on evidence-based explanations and evaluation experiences in teacher education and professional development is also crucial as it is practiced and experienced in the real world. In this study, we investigate how pre-service science teachers incorporated nature of science aspects and used evidence-based explanation in their lesson plans. The findings of this study suggest that enabling pre-service teachers to design lesson plans for the use of competing theories may guide them to enable their students to engage in arguments from evidence and evaluate the trustworthiness of these evidences in a discourse environment. The results also indicate the necessity of explicit teaching of nature of science through instructional scaffolds that promote evaluation of evidence-based explanations.